Comparing epidural surgical anesthesia and spinal anesthesia following epidural labor analgesia for intrapartum cesarean section: a prospective randomized controlled trial - Yoon, Hea-Jo (Korean J Anesthesiol, 2017)
BACKGROUND: The conversion of epidural labor analgesia (ELA) to epidural surgical anesthesia (ESA) for intrapartum cesarean section (CS) often fails, resulting in intraoperative pain. Spinal anesthesia (SA) can provide a denser sensory block than ESA. The purpose of this prospective, non-blinded, parallel-arm, randomized trial was to compare the rate of pain-free surgery between ESA and SA following ELA for intrapartum CS. METHODS: Both groups received continuous epidural infusions for labor pain at a rate of 10 ml/h. In the ESA group (n = 163), ESA was performed with 17 ml of 2% lidocaine mixed with 100 µg fentanyl, 1 : 200,000 epinephrine, and 2 mEq bicarbonate. In the SA group (n = 160), SA was induced with 10 mg of 0.5% hyperbaric bupivacaine and 15 µg fentanyl. We investigated the failure rate of achieving pain-free surgery and the incidence of complications between the two groups. RESULTS: The failure rate of achieving pain-free surgery was higher in the ESA group than the SA group (15.3% vs. 2.5%, P < 0.001). There was no statistical difference between the two groups in the rate of conversion to general anesthesia; however, the rate of analgesic requirement was higher in the ESA group than in the SA group (12.9% vs. 1.3%, P < 0.001). The incidence of high block, nausea, vomiting, hypotension, and shivering and Apgar scores were comparable between the two groups. CONCLUSIONS: SA after ELA can lower the failure rate of pain-free surgery during intrapartum CS compared to ESA after ELA.